2024
DOI: 10.1186/s40001-024-01655-4
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a nomogram for predicting in-hospital mortality of patients with cervical spine fractures without spinal cord injury

Zhibin Xing,
Lingli Cai,
Yuxuan Wu
et al.

Abstract: Background The incidence of cervical spine fractures is increasing every day, causing a huge burden on society. This study aimed to develop and verify a nomogram to predict the in-hospital mortality of patients with cervical spine fractures without spinal cord injury. This could help clinicians understand the clinical outcome of such patients at an early stage and make appropriate decisions to improve their prognosis. Methods This study included 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Further, a prospective study involving 290 participants showed that in elderly patients who underwent hip fracture surgery, a strong association was observed between SII and increased mortality due to any cause ( 5 ). In addition, several studies have demonstrated the role of SII in reflecting systemic inflammation and disease severity ( 36 , 37 ), particularly the diagnostic significance of SAPSII in orthopedic diseases ( 38 , 39 ). These studies suggested that SII showed potential for predicting clinical outcomes in critically ill elderly individuals with hip fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a prospective study involving 290 participants showed that in elderly patients who underwent hip fracture surgery, a strong association was observed between SII and increased mortality due to any cause ( 5 ). In addition, several studies have demonstrated the role of SII in reflecting systemic inflammation and disease severity ( 36 , 37 ), particularly the diagnostic significance of SAPSII in orthopedic diseases ( 38 , 39 ). These studies suggested that SII showed potential for predicting clinical outcomes in critically ill elderly individuals with hip fractures.…”
Section: Discussionmentioning
confidence: 99%